Acute Care Pharmacy Practice: A Perspective for Pharmacy Students, Residents, and Other Health-Care Providers. (June 2020) - Dunn, Rebecca L.; Cho, Jonathan C.; Parmentier, Brittany L.
Purpose: To describe the acute care setting with a specific focus on acute care pharmacy practices. Summary: Acute care is the sector of health care where time-sensitive episodes of illness are managed. Acute care pharmacy practice includes both hospital and clinical pharmacists serving, in a variety of domains, as medication experts and authority on patient-centered medication therapy. Pharmacists serving in this area can have a beneficial impact on patient care and the health-care system. Conclusion: The demand for acute care services is likely to grow as the population continues to grow and age. Pharmacists are key members of interdisciplinary teams in the acute care setting.